Lamiyiat Ash-shanfara The Dynamic Polarity In Presence-Absence Relationships - Nassif, Nassif Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This piece of research attempts to trace the textual study through examining the excellencies of Ash-shanfara’s text, next to its artistic secrecies that have been neglected by those researches who were busy with stories, tales, language and (ideology). However, the literary heritage has received a considerable amount folkloric tales and superstitions. In the past, linguists had been attracted to the al-Lamiyiah semantically and syntactically. A few contemporary studies had mentioned few selections, the thing that triggered the sence of poetical in their veins, which found it enough to portray a constellation of its intellectual proposals. Thus al-Lamiyiah survived, being an artistic masterpiece a virgin soil. Henceforward comes this research to scrtunize the strata of secrets of artistic aesthetics, starting from the dynamic polarity structure that systematize the concluded presence-absence relationships, and ending with crystallizing the poetical personality (not the historical) in the poetical heritage. It unleashes the varieties of the ‘ego’ within its unique tissue ascertaining the poetry is creativity, and not merely virgin before natural scenaries, or successive episodes through time, nether is it a description per se. Rather, it is an intuitive creation that manipulates nature, among many other things, for the sake of its artistic intentions.